Arc flash hazard analysis and mitigation - Das, J. C., 1934- (IEEE Press series on power engineering., 2012)
"All the aspects of arc flash hazard calculations and their mitigation have been covered. Knowledge of electrical power systems up to undergraduate level is assumed. The calculations of short-circuits, protective relaying and varied electrical system configurations in industrial power systems are addressed. Protection systems address differential relays, arc flash sensing relays, protective relaying coordination, current transformer operation and saturation and applications to major electrical equipments from the arc flash considerations. Current technologies and strategies for arc flash mitigation have been covered. A new algorithm for the calculation of arc flash hazard accounting for the decaying nature of the short-circuit currents is included. There are many practical examples and study cases. Review questions and references follow each chapter"--